Carbon, Nitrogen and Sulphur isotopic fractionation in captive juvenile hooded seal (Cystophora cristata): application for diet analysis - Pinzone, Marianna; Acquarone, Mario; Huyghebaert, Loreen; Sturaro, Nicolas; Michel, Loïc N.; Siebert, Ursula; Das, Krishna (Rapid Communications in Mass Spectrometry, 2017)
This is the peer reviewed version of the following article: Pinzone, M., Acquarone, M., Huyghebaert, L., Sturaro, N., Michel, L.N., Siebert, U. & Das, K. (2017). Carbon, Nitrogen and Sulphur isotopic fractionation in captive juvenile hooded seal (Cystophora cristata): application for diet analysis. Rapid Communications in Mass Spectrometry , 31(20). https://doi.org/10.1002/rcm.7955, which has been published in final form at https://doi.org/10.1002/rcm.7955 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Rationale : Intrinsic biogeochemical markers, such as stable isotope ratios of carbon, nitrogen and sulphur, are increasingly used to trace the trophic ecology of marine top predators. However, insufficient knowledge of fractionation processes in tissues continues to hamper the use of these markers. Methods : We performed a controlled feeding experiment with eight juvenile hooded seals ( Cystophora cristata ) that were held on a herring‐based diet ( Clupea harengus ) for two years. Stable isotope ratios were measured via isotope ratio mass spectrometry in three of their tissues and related to values of these markers in their diet. Results : Diet‐tissue isotope enrichment (trophic enrichment factor, TEF) values between dietary herring and seal tissues for carbon (Δ 13 C) were +0.7 ‰ for red blood cells, +1.9 ‰ for hair and +1.1 ‰ for muscle. The TEFs for nitrogen trophic (Δ 15 N) were +3.3 ‰ for red blood cells, +3.6 ‰ for hair and +4.3 ‰ for muscle. For sulphur, the Δ 34 S values were +1.1 ‰ for red blood cells, +1.0 ‰ for hair and +0.9 ‰ for muscle. Conclusions : These enrichment values were greater than those previously measured in adult seals. This increase may be related to the higher rate of protein synthesis and catabolism in growing animals. This study is the first report on sulphur isotope enrichment values for a marine mammal species.